Synthesis and Characterization of Perovskite Manganate Based on La0.7Ca0.3MnO3 with Ni and Ti doping as Microwave Absorber Material - Saptari, Sitti Ahmiatri; Mar’ah, Mufidatul; Taryana, Yana; Sudrajat, Nanang (Science and Technology Indonesia, 2024)
Research has been carried out on the effect of Ni and Ti doping on the microwave absorption properties of the perovskite manganate material La0.7Ca0.3Mn1-xNix/2Tix/2O3 (LCMNTO) with variations x = 0; 0.03; 0.05; and 0.1, which were synthesized by the sol-gel method. The effect of Ni and Ti doping on the structure, grain size, magnetic properties, and microwave absorption properties were investigated in detail by various analytical methods. XRD (x-ray diffraction) characterization showed that the material La0.7Ca0.3Mn1-xNix/2Tix/2O3 has a single phase with an orthorhombic crystal system. The SEM (scanning electron microscope) results showed a tendency to decrease in grain size when the composition of Ni and Ti dopants began to increase. VSM (vibrating sample magnetometer) characterization shows that La0.7Ca0.3Mn1-xNix/2Tix/2O3 is a soft magnet with magnetic properties that decrease with increasing Ni and Ti dopant composition. The characterization of VNA (vector network analyzer) in the 8-12 GHz shows that the highest ability to absorb microwaves is 98% at 8.24 GHz, and there is an addition of absorption areas point and widening of the absorption bandwidth. Thus, the material La0.7Ca0.3Mn1-xNix/2Tix/2O3 has the potential to become a microwave absorber material.